2005
DOI: 10.1016/j.immuni.2005.03.004
|View full text |Cite|
|
Sign up to set email alerts
|

Syk-Dependent Cytokine Induction by Dectin-1 Reveals a Novel Pattern Recognition Pathway for C Type Lectins

Abstract: Pattern-recognition receptors (PRRs) detect molecular signatures of microbes and initiate immune responses to infection. Prototypical PRRs such as Toll-like receptors (TLRs) signal via a conserved pathway to induce innate response genes. In contrast, the signaling pathways engaged by other classes of putative PRRs remain ill defined. Here, we demonstrate that the beta-glucan receptor Dectin-1, a yeast binding C type lectin known to synergize with TLR2 to induce TNF alpha and IL-12, can also promote synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

43
798
4
16

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 816 publications
(861 citation statements)
references
References 44 publications
43
798
4
16
Order By: Relevance
“…Thus, one would predict that lack of Syk and/or BTK in DC affects Dectin-1-mediated inflammatory cytokine production, as PLCg2-deficiency does. Accordingly, a previous study showed that lack of Syk impairs Dectin-1 function [8,9,18]. To further extend this study, we asked whether BTK is required for cytokine responses to b-glucan.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, one would predict that lack of Syk and/or BTK in DC affects Dectin-1-mediated inflammatory cytokine production, as PLCg2-deficiency does. Accordingly, a previous study showed that lack of Syk impairs Dectin-1 function [8,9,18]. To further extend this study, we asked whether BTK is required for cytokine responses to b-glucan.…”
mentioning
confidence: 91%
“…Another downstream ITAM mediator, PI-3K, activates PLCg by generating phosphatidylinositol 3,4,5 trisphosphate, which binds the pleckstrin homology domain of PLCg, promoting PLCg recruitment to the cell membrane. Thus, the ability of Dectin-1 to initiate an ITAM-Syk-signaling pathway [9] provides a rationale for studying the role of PLCg in Dectin-1-mediated antimicrobial responses in DC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling through an immunoreceptor tyrosinebased activation motif (ITAM)-like motif allows dectin-1 to generate inflammatory responses in addition to its role as a phagocytosis receptor. Ligand binding results in phosphorylation of the ITAM motif, leading to the activation of the downstream tyrosine kinase Syk, CARD9 and initiation of phagocytosis, respiratory burst and production of the cytokines IL-2 and 26].…”
Section: Introductionmentioning
confidence: 99%
“…Signaling through an immunoreceptor tyrosinebased activation motif (ITAM)-like motif allows dectin-1 to generate inflammatory responses in addition to its role as a phagocytosis receptor. Ligand binding results in phosphorylation of the ITAM motif, leading to the activation of the downstream tyrosine kinase Syk, CARD9 and initiation of phagocytosis, respiratory burst and production of the cytokines IL-2 and 26].In addition to dectin-1 and TLR2, complement receptors such as CR3 have also been shown to bind directly to non-opsonized zymosan via their lectin domains [27,28]. In addition, SIGNR1 [29] and the mannose-receptor (MR) can also bind fungal components, but these receptors are mainly expressed by macrophages [11,30,31].…”
mentioning
confidence: 99%